2021
DOI: 10.1002/aic.17156
|View full text |Cite
|
Sign up to set email alerts
|

Impact of defects on the decomposition of chemical warfare agent simulants in Zr‐based metal organic frameworks

Abstract: Metal organic frameworks (MOFs) containing zirconium secondary building units (SBUs) in UiO-67 and related MOFs, are highly active for neutralizing both the chemical warfare agents and simulants, such as dimethyl methylphosphonate (DMMP). However, two recent publications gave conflicting reports of DMMP reaction with UiO-67 under ultra high vacuum (UHV) conditions, with one reporting chemisorption and reaction (Wang et al.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Carboxylate-based zirconium-MOFs have been proved to own outstanding chemical stability, whose structures can be easily adjusted by finely choosing the organic linkers. [28][29][30] Herein, MOF-801 was selected as the membrane materials which is consisting of the Zr 6 O 4 (OH) 4 secondary building unit (SBU) and fumaric acid organic linker (Figure S1), usually also known as Zr-fum-fcu-MOF. 31 Each Zr 6 O 4 (OH) 4 SBU is coordinated to 12 fumarate linkers, which forms interconnected tetrahedral and octahedral cavities with a 3.5 Å theoretical triangular window (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carboxylate-based zirconium-MOFs have been proved to own outstanding chemical stability, whose structures can be easily adjusted by finely choosing the organic linkers. [28][29][30] Herein, MOF-801 was selected as the membrane materials which is consisting of the Zr 6 O 4 (OH) 4 secondary building unit (SBU) and fumaric acid organic linker (Figure S1), usually also known as Zr-fum-fcu-MOF. 31 Each Zr 6 O 4 (OH) 4 SBU is coordinated to 12 fumarate linkers, which forms interconnected tetrahedral and octahedral cavities with a 3.5 Å theoretical triangular window (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…A MOF membrane with high chemical stability and appropriate pore size is very necessary for the VFB system. Carboxylate‐based zirconium‐MOFs have been proved to own outstanding chemical stability, whose structures can be easily adjusted by finely choosing the organic linkers 28–30 . Herein, MOF‐801 was selected as the membrane materials which is consisting of the Zr 6 O 4 (OH) 4 secondary building unit (SBU) and fumaric acid organic linker (Figure S1), usually also known as Zr‐fum‐fcu‐MOF 31 .…”
Section: Resultsmentioning
confidence: 99%
“…Despite the 1993 Chemical Weapons Convention, which outlaws the production and use of chemical weapons and their precursors, the use of CWAs remains a threat. There have been many experimental and theoretical investigations conducted recently on the usage of MOFs for capture and decomposition of CWAs. In particular, several zirconium-based MOFs have been concluded to be efficient materials for capturing sarin, one of the most toxic CWAs.…”
Section: Introductionmentioning
confidence: 99%
“…34 Computational studies have also been helpful in probing mechanisms of simulant and agent hydrolysis. [42][43][44] Using density functional theory (DFT), Chen et al investigated the complete catalytic cycle of the NU-1000 catalyzed hydrolysis of simulant DMNP. 42 Their analysis of intermediate and transition-state structures revealed that the catalytic effects of NU-1000 nodes originate with an aqua ligand (Zr-OH2) being displaced by the simulant molecule and bound to Zr(IV), Lewis-acid activation of the P=O bond is followed by the nucleophilic hydroxide ion from the solution attacking the phosphate ester of the simulant or the P-F bond of the real nerve-agent (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%